Devolution, market dynamics and the Independent Public School initiative in Western Australia: 'winning back' what has been lost?. Issue 5 (3rd September 2018) - Fitzgerald, Scott; Stacey, Meghan; McGrath-Champ, Susan; Parding, Karolina; Rainnie, Al
Abstract: The devolution of public sector schooling systems has been a feature of education reform since the 1980s. In Western Australia, the Independent Public School (IPS) initiative has recently been installed, announced by the state government in 2009. Now over 80% of the state's public school students attend IP schools. Drawing on interview data from a broader study of devolution and the conditions of teachers' work, this article explores the cases of two schools – one IPS and one non-IPS. While both schools were ostensibly disadvantaged, they proved to be highly contrasting schooling sites, responding to the school marketplace in markedly different ways. We consider the ways in which the IPS initiative is contributing to the operation of market dynamics within the public school sector in WA, and argue that it has created new mechanisms for the residualisation of particular, and specifically non-IP, schools. Furthermore, while one school was apparently more of a 'winner' within the school marketplace, as it was attracting increasing student enrolments, we query what it might actually mean to 'win' in such a policy settlement, with staff at both schools reporting significant dissatisfaction in their work.